2020
DOI: 10.1002/jctb.6377
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient removal by alginate‐immobilized Chlorella vulgaris: response to different wastewater matrices

Abstract: BACKGROUND: Immobilized algae are a promising tool to treat wastewater within a short time (<12 h) and simplify biomass harvesting compared with suspended algae. The potential of alginate-entrapped Chlorella vulgaris to bioremediate secondary (with and without nutrient supplementation), primary and two lagoon municipal wastewaters was investigated. The capability of the system to adapt to these wastewaters was analysed by determining biotic and abiotic nutrient removal, and further evaluated by comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Another widely researched wastewater treatment reactor configuration is the active immobilized algal bead systems. These reactors resemble the enclosed suspended growth systems with the difference that the algal cells do not float freely into the water medium but are encapsulated into separate beads with specific a biomass concentration inside [39,54]. The beads are preliminarily prepared in a laboratory setting, either through covalent bonding, adsorption, semi-permeable membrane encasing, or polymer enfolding (Figure 5) [39,54,55].…”
Section: Algal Bead Systems (Active Immobilization)mentioning
confidence: 99%
See 2 more Smart Citations
“…Another widely researched wastewater treatment reactor configuration is the active immobilized algal bead systems. These reactors resemble the enclosed suspended growth systems with the difference that the algal cells do not float freely into the water medium but are encapsulated into separate beads with specific a biomass concentration inside [39,54]. The beads are preliminarily prepared in a laboratory setting, either through covalent bonding, adsorption, semi-permeable membrane encasing, or polymer enfolding (Figure 5) [39,54,55].…”
Section: Algal Bead Systems (Active Immobilization)mentioning
confidence: 99%
“…These reactors resemble the enclosed suspended growth systems with the difference that the algal cells do not float freely into the water medium but are encapsulated into separate beads with specific a biomass concentration inside [39,54]. The beads are preliminarily prepared in a laboratory setting, either through covalent bonding, adsorption, semi-permeable membrane encasing, or polymer enfolding (Figure 5) [39,54,55]. The main reason for the development of such technology is the mitigation of the post-treatment algal harvesting and higher control over the algal monoculture contamination [39,54].…”
Section: Algal Bead Systems (Active Immobilization)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, beads produced by immobilized microalgae can also shield the culture from harmful contaminants in wastewater [109]. Kube [110] demonstrated that different concentrations of nitrogen and phosphorus can influence the absorption of phosphorus by Chlorella and that the immobilization of microalgae does not hinder the rate or ratio of nitrogen and phosphorous absorption. In addition, cell immobilization and co-cultivation of Bacillus vulgaris and P. brasiliensis can boost the removal rates of ammonia and phosphorus [111].…”
Section: Immobilized Recovery Technologymentioning
confidence: 99%
“…Furthermore, C. vulgaris has been successfully used for bioremediation of different wastewater sources due to its robustness, mixotrophic culturing conditions, high growth rate under harsh conditions, and tolerance to high levels of heavy metals (Ge et al, 2013). However, work by Kube et al (2020) suggests that certain environmental conditions may play an inhibitory role in nutrient accumulation. Further, it is possible the immobilization medium could be destabilized in some aquatic conditions (Mohseni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%